Economic and energy evaluation of biomass/coal-to-energy in China: Analysis from China soybean industry. Issue 11 (2nd November 2017) - Tianbao, Guo; Yunfeng, Wang
ABSTRACT: There are many thermal or biological methods for the utilization of biomass such as combustion, gasification, and pyrolysis. Gasification is a thermochemical conversion method that converts carbon-based fuels (solid and liquid) into a high-caloric-value syngas via partial oxidation. In this article, to investigate the influence of plant capacity on installed capital cost and stoichiometric ratio (SR) on gas composition and gas caloric value, an Aspen Plus model was developed where it was assumed that the reactions operate under steady-state conditions. With increasing SR from 0.2 to 0.8, the caloric value of the produced gas decreased sharply for both fuels due to a significant reduction in the concentration of H2, CO, and CH4 . In addition, for higher plant capacities, the installed capital cost showed a constant rate, because it depends strongly on the individual capital costs of equipment and the capacity cost plays a minor role.